2014
DOI: 10.1007/s12282-014-0539-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating tumor cells (CTCs) with respect to optimal cut-off value and tumor markers in advanced/metastatic breast cancer

Abstract: We found that a CTC cut-off value of 1 is appropriate in patients with advanced/metastatic breast cancer. CTCs could yield additional information beyond CEA and CA15-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…13,14 Second, there is no consensus about the cutoff value for diagnosis and prognosis. [15][16][17] Finally, most studies are based on the CellSearch platform because it is the only United States Food and Drug Administrationapproved platform currently, but the CellSearch platform has been shown to have a number of limitations. Indeed, the CellSearch platform is based on the restricted phenotypic definition of a CTCs (cells of epithelial origin expressing cytokeratin but not CD45) and so excludes many classes of informative cells because the system only allows for the detection of CK þ CD45 À cells and does not allow customization for the detection of other cellular characteristics, such as the expression of HER2, estrogen receptor, and progesterone receptor.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Second, there is no consensus about the cutoff value for diagnosis and prognosis. [15][16][17] Finally, most studies are based on the CellSearch platform because it is the only United States Food and Drug Administrationapproved platform currently, but the CellSearch platform has been shown to have a number of limitations. Indeed, the CellSearch platform is based on the restricted phenotypic definition of a CTCs (cells of epithelial origin expressing cytokeratin but not CD45) and so excludes many classes of informative cells because the system only allows for the detection of CK þ CD45 À cells and does not allow customization for the detection of other cellular characteristics, such as the expression of HER2, estrogen receptor, and progesterone receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CTCs measured prior to any new treatment constitute independent prognostic markers that could supplement the currently used clinical predictive biomarkers of breast cancer. It is also noteworthy that predicted disease progression was more accurate when based on measurement of CTC levels after the initiation of therapy, compared to predictions based on levels of tumor markers recommended for monitoring metastatic breast cancer according the international guidelines (e.g., CEA, CA15-3) [51]. This is the first analysis carried out in a large group of patients in Europe, and demonstrates the utility of CTCs in monitoring the progression of distant metastatic breast cancer, and accurately determining the risk of disease progression in a given patient.…”
Section: Clinical Application Of Ctcs: Summarymentioning
confidence: 99%
“…Moreover, detection of CK‐19 mRNA + CTCs after adjuvant chemotherapy is an independent risk factor for shorter DFS ( p < 0.001) and OS ( p = 0.003) . Simply put, detection of CTCs in both early and advanced stage BC can identify patients with worse prognoses than controls (Tables and ). Georgoulias et al .…”
Section: Ctcs May Be Used As a Valuable Prognostic And Predictive Biomentioning
confidence: 99%
“…Moreover, detection of CK-19 mRNA 1 CTCs after adjuvant chemotherapy is an independent risk factor for shorter DFS (p < 0.001) and OS (p 5 0.003). 107 Simply put, detection of CTCs in both early 6,39,104-106,108-115 and advanced 36,[40][41][42][43]46,61,102,103,113,[116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] stage BC can identify patients with worse prognoses than controls (Tables 2 and 3). Georgoulias et al reported that the paradigm of Herceptin-treated patients based on their and c-erbB2, TFF1, CK19, ERb…”
Section: Ctcs May Be Used As a Valuable Prognostic And Predictive Biomentioning
confidence: 99%